HIF-PHIs associated with embolic and thrombotic events: a real-world pharmacovigilance study based on the Japan Adverse Drug Event Report database - Danna Wu; Shuxin Jiao; Hongru Lin; Peitao Xie; Guohao Cai; Mingdao Lin (Renal Failure)
Background Hypoxia-inducible factor prolyl hydroxylase inhibitors (HIF-PHIs) play an important role in the treatment of renal anemia. However, some studies suggest a potential link between HIF-PHIs and increased thrombosis risk, though these findings are inconsistent and lack large-scale clinical support. We aim to summarize embolic and thrombotic events associated with HIF-PHIs in different populations in real world, especially among high-risk patients.Methods Using the Japan Adverse Drug Event Report (JADER) database from January 1, 2020, to September 30, 2023, a disproportionality analysis was employed to identify embolic and thrombotic events associated with HIF-PHIs using the reporting odds ratios (ROR) and information component (IC). We also evaluated the time to onset among different populations.Results From January 2020 to September 2023, the JADER database reported a total of 253,599 cases, including 1,222 cases of embolic and thrombotic events, which represented 30.44% of all HIF-PHIs reported. Embolic and thrombotic events (ROR = 6.68) related to HIF-PHIs is positive signal, with the strongest signal observed for vessel type unspecified and mixed arterial and venous (ROR = 7.97). The signal intensity is higher in females than in males (p = 0.008) and also greater in the non-dialysis population compared to the dialysis population (p < 0.001). The median onset time was shorter in the dialysis population than in the non-dialysis population (days: 27 vs. 47, p = 0.016).Conclusion Attention to embolic and thrombotic events associated with HIF-PHIs is essential, with careful selection of specific types based on underlying diseases, sex, age, and indications.